CEOs' International Work Experience and Compensation - Stefan Schmid; Sebastian Baldermann (Management International Review, 2021)
In this paper, we study the effect a CEO's international work experience has on his or her compensation. By combining human capital theory with a resource dependence and a resource-based perspective, we argue that international work experience translates into higher pay. We also suggest that international work experience comprises several dimensions that affect CEO compensation: duration, timing and breadth of stays abroad. With data from Europe's largest stock market firms, we provide evidence that the longer the international work experiences and the more numerous they are, the higher a CEO's compensation. While, based on our theoretical arguments, we expect to find that later international work experiences pay off for CEOs, our empirical analysis shows that earlier international work experiences are particularly valuable in terms of compensation. In addition, our data support the argument that maturity allows a CEO to take advantage of the skills, knowledge and competencies obtained via international experience—and to receive a higher payoff. With our study, we improve the understanding of how different facets of a CEO's background shape executive remuneration.
Keywords: 330; Executive compensation; Human capital theory; Resource dependence theory; Resource-based view; International top managers; International experience; International work experience; Maturity; Cultural distance